2004
DOI: 10.1016/j.femsec.2004.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic characterization and plant colonizing abilities of some bacteria related to Bacillus amyloliquefaciens and Bacillus subtilis

Abstract: The phylogenetic relationships of 17 Bacillus strains isolated from plants and soil were determined from partial sequences of genes encoding 16S rRNA, gyraseA (gyrA) and the cheA histidine kinase. Five strains were closely related to Bacillus subtilis subsp. subtilis, three strains were more closely related to B. subtilis subsp. spizizeni and two strains were identified as B. mojavensis. The remaining seven strains formed a cluster closely related to, but distinct from, Bacillus amyloliquefaciens. Some of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
113
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(122 citation statements)
references
References 41 publications
7
113
0
2
Order By: Relevance
“…The resulting phylogenetic trees ( Supplementary Fig. 4 online) revealed that B. amyloliquefaciens FZB42 is rather close to strains recently introduced as endophytic or plant-associated ecomorphs of B. amyloliquefaciens 41 . Essentially all Bacillus strains that are currently commercialized for their plant growth-promoting and biocontrol activities belong to this ecotype.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting phylogenetic trees ( Supplementary Fig. 4 online) revealed that B. amyloliquefaciens FZB42 is rather close to strains recently introduced as endophytic or plant-associated ecomorphs of B. amyloliquefaciens 41 . Essentially all Bacillus strains that are currently commercialized for their plant growth-promoting and biocontrol activities belong to this ecotype.…”
Section: Discussionmentioning
confidence: 99%
“…Successful plant colonization by PGPR relied on multiple factors including but not limited to withstanding environmental stress (Reva et al, 2004), efficient chemotaxis (Yssel et al, 2011), effective communication within the bacterial communities and between bacteria and plants carried out by synthesized plant hormones and quorum sensing autoinducers (Lengeler & Postma 1999;Farag et al, 2013). All the factors are directly or indirectly related to effective sensing of environmental signals and proper regulation of gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it was shown in experiments that in trans complementation of E. coli cells with knocked out chemotaxis proteins CheA and CheB with their counterparts from B. subtilis rescued the mutation (Garrity and Ordal 1995). It was shown in a previous study, that CheA is quite variable even on the level of subspecies of bacteria of B. subtilis group (Reva et al 2004). …”
Section: Introductionmentioning
confidence: 99%
“…They are commonly referred to as the B. subtilis group. Members of this group are free-living soil micro-organisms but several strains of B. amyloliquefaciens and B. subtilis are plant growth promoting rhizobacteria (PGPR) (Reva et al 2004). It has been shown that different strains of members of the B. subtilis group exhibit different specificity towards certain host plants (Reva et al 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation